2019
DOI: 10.1002/adma.201903878
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Supraparticles for Controllable Nanomedicine

Abstract: Chirality is ubiquitous in nature and hard-wired into every biological system. Despite the prevalence of chirality in biological systems, controlling biomaterial chirality to influence interactions with cells has only recently been explored. Here, we present chiral-engineered supraparticles (SPs) that interact differentially with cells and proteins depending on their handedness. SPs coordinated with Dchirality demonstrated greater than three-fold enhanced cell membrane penetration in breast, cervical, and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
140
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 53 publications
0
140
0
Order By: Relevance
“…The most important biological macromolecules in life, such as sugars, protein, and nucleic acids, are all chiral (Milton et al, 2016 ). Therefore, chirality is widely concerned in scientific research, including drug recognition (Zhou et al, 2018 ), physiological activities (Wei et al, 2014 ), material preparation (Chen et al, 2019 ), enantioselective reactions (Yutthalekha et al, 2016 ), and pharmaceutical science (Yeom et al, 2020 ). Nanomaterials have broad application prospects in biosensors and biomedical fields due to their surface effect and small size effect (Albanese et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most important biological macromolecules in life, such as sugars, protein, and nucleic acids, are all chiral (Milton et al, 2016 ). Therefore, chirality is widely concerned in scientific research, including drug recognition (Zhou et al, 2018 ), physiological activities (Wei et al, 2014 ), material preparation (Chen et al, 2019 ), enantioselective reactions (Yutthalekha et al, 2016 ), and pharmaceutical science (Yeom et al, 2020 ). Nanomaterials have broad application prospects in biosensors and biomedical fields due to their surface effect and small size effect (Albanese et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yeom et al. 44 found that d -forms of chiral drugs or excipients can better enter tumor cells. BAD may lead to a higher inhibition rate than BAL to the A549 cell line at 24 h due to its better access to tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these novel D-chiral SPs, composed by Dcystein capped cobalt-oxide NPs, demonstrated higher resistance to enzymatic digestion and a more enhanced tumour killing efficiency with respect to L-chiral and racemic analogous SPs. 79 It is also clear that NP self-assembly, beyond providing a huge space to host molecular guests and enhanced porosity, produces complex SPs with efficient multifunctionality and often responsivity to exogenous (e.g., light, magnetic field, ultrasound, etc.) or endogenous (e.g., pH, enzyme, ionic strength, etc.)…”
Section: Carriers and Biomedical Systemsmentioning
confidence: 99%